Dehydration of cavendish banana (Musa cavendishii) - Angeles, Regina A. (1979)
Dehydrated banana was developed from Cavendish banana using the improvised cabinet drier. Results of the study showed that a product could be developed by immersing the ripe fruit slices of 2 to 2 1/2 inches long in 1.6% Na2S2O5 for 15 minutes and drying these slices for 9 hours at 160°F in the cabinet drier for the first day and stored in the refrigerator. The next day, they are dried for an additional 2 hours at the same temperature. The product may have a final moisture content ranging from 8% to 15%, a sweet banana flavor, a color ranging from golden yellow to golden brown and texture from "firm and dry" to "tender and moist".